Planning for urban biodiversity on shifting social–ecological grounds: Insights from Narrm‐Melbourne, Australia - Dave Kendal; Judy Bush (Ecological Solutions and Evidence)
Abstract Narrm‐Melbourne, Australia, has been at the forefront of urban biodiversity research, planning and management for 50 years in urban landscapes that have many endemic and threatened species and remnant ecosystems. Yet a range of emerging social and ecological challenges are emerging that must be addressed for Narrm‐Melbourne to continue to be a leader in urban biodiversity planning and practice. Drawing on key insights from this work and our own experience working in research and practice, we explore three dimensions of urban biodiversity planning—land‐use planning, open space planning and conservation planning. Key challenges currently being experienced include greater recognition of ecosystems as cultural landscapes and Traditional Owner rights, knowledge and practices; climate change and urban heat; and greater participation of a multicultural general public. These challenges also provide opportunities for achieving positive biodiversity outcomes at multiple scales that are consistent with the goals and targets of the Global Biodiversity Framework. Practical implication. Innovations to the planning system that could help achieve these positive outcomes include decolonising biodiversity planning by recognising the cultural determinants of current ecosystem structure and function, and involving Traditional Owners in co‐management of urban landscapes. A greater focus on ecosystem function, resilience and connected multifunctional habitats will allow the planning system to move beyond its historic and conventional focus on local species and community composition. And finally, greater participation by and engagement with diverse local communities will increase diversity in decision‐making and can contribute to resilience and function.